Dampak Monopoli Jasa Pengiriman dalam E-commerce terhadap Hak Konsumen: Kajian Peran Lembaga Perlindungan Konsumen - Vito Jonathan Octavo; Ariawan Gunadi (Dinasti Research, 2024)
Technological advances have driven major changes in various sectors, including the economy, through the digitalization of trade known as e-commerce. E-commerce introduces virtual interactions between producers and consumers, offering the convenience of efficient transactions. However, this phenomenon also raises new challenges, such as the potential for monopoly of delivery services that can harm consumers. This practice often limits consumers' rights to choose services such as delivery services according to their needs. This study aims to analyze the impact of monopoly of delivery services by e-commerce on consumer rights in Indonesia, as well as review the role of consumer protection institutions. Based on a normative approach with a prescriptive analysis method.